Investigação do perfil genotípico de indivíduos com Fibrose Cística em uma população miscigenada do Centro-Oeste brasileiro - (:unkn) unknown (Universidade Estadual de Goiás, 2022)
Cystic Fibrosis (CF) is an autosomal recessive disease caused by a mutation in the CFTR gene which provides an alteration in the CFTR protein that is responsible for the conduction of chloride and bicarbonate in epithelial tissues. This disease is associated with an accented morbidity that varies according to the mutation in each patient. Protein changes which are categorized according to mutation classes and they are associated with disease’s phenotypes ranked from mild to severe. This study aims to analyze the applicability CFTR gene’s molecular markers in the CF’s assessment. To reach the main goal of this work, the dissertation is structured in four articles. The first article is a literature review on the structural aspects of the CFTR gene. The databases used for the research were: PubMed, LILACS (Latin American and Caribbean Literature in Health Sciences), MEDLINE (International Literature in Health Sciences and Biomedical). From the 1,418 articles found on these platforms 24 of them mentioned the CFTR gene’s structure. The CFTR gene’s structure and morphology description and its association of the exons with its respective encoded domains in the CFTR protein were performed. Mutations in the gene affect the CF’s pathophysiology. The second article describes the main mutations found in a CF referral center in Goiânia. It was a cross-sectional, descriptive study in which data were collected frommedical records. The study showed a high heterogeneity of the patients analyzed and, thisallelotypic and genotypic profiles differs from the profiles described in other parts of Brazil,mainly from population with little miscegenated data. The third article is a systematic review of the literature which aims to investigate the association among silencing the CFTR gene by anepigenetic pathway, methylation, which is independent of the mutated gene in CF patients. Thisquestion was based on patients with symptoms that characterize CF, but with a negative orinconclusive genetic test. The research was done in Pubmed, Scopus and Web of Science databases. A total of 316 articles were selected and, after applying the eligibility criteria, four articles were also included. The systematic review allowed us to conclude that the epigenetic pathway by methylation is not intrinsic to the CF’s etiology. The fourth article aims to evaluate lung function and its performance in the six-minute walk test of children with CF and to correlatewith clinical variables. It was a cross-sectional, analytical study carried out in a reference centerfor Cystic Fibrosis in the city of Goiânia. A total of 20 children with CF followed up at theoutpatient clinic were selected to participate in the study. The medium age was 10.4 years old;they were most female (70%) and the distance covered 489.81meters in the walking test of 6minutes. The average was FEV1: 73.76%, FVC: 81.88%. The children and adolescents withcystic fibrosis in this sample covered a shorter distance when compared to healthy children and adolescents. And the age variables have a direct relationship, while FEV1 and BMI are inverse with distance.
Investigation of the genotypic profile of individuals with Cystic Fibrosis in a mixed population of the Brazilian Midwest
Keywords: Mucoviscidose; Proteína CFTR; Heterogeneidade genética; Mutação; Fenótipo; Epigenétic; Fibrose Cística (FC); Mucoviscidosis; CFTR protein; Mutation; Phenotype; Epigenetics; OUTROS; CIENCIAS DA SAUDE